2018
DOI: 10.1128/jvi.00181-18
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Mediates the Localization of Measles Virus Matrix Protein at the Plasma Membrane

Abstract: Annexins are a family of structurally related proteins that bind negatively charged membrane phospholipids in a Ca-dependent manner. Annexin A2 (AnxA2), a member of the family, has been implicated in a variety of cellular functions including the organization of membrane domains, vesicular trafficking and cell-cell adhesion. AnxA2 generally forms the heterotetrameric complex with a small Ca-binding protein S100A10. Measles virus (MV), a member of the family , is an enveloped virus with a nonsegmented negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…However, interactions of 14-3-3 proteins with EBOV have not been reported previously. Similarly, annexin family proteins also interact closely with RNA viruses such as measles virus and H5N1 avian influenza virus ( Ma et al, 2017 ; Koga et al, 2018 ), but interactions with EBOV have not been reported previously. MAP kinases are essential in signal transduction and involved in numerous virus life cycle events, including in EBOV ( Strong et al, 2008 ; Johnson et al, 2014 ), but the detailed mechanisms of interactions between MAP kinases and EBOV remain ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…However, interactions of 14-3-3 proteins with EBOV have not been reported previously. Similarly, annexin family proteins also interact closely with RNA viruses such as measles virus and H5N1 avian influenza virus ( Ma et al, 2017 ; Koga et al, 2018 ), but interactions with EBOV have not been reported previously. MAP kinases are essential in signal transduction and involved in numerous virus life cycle events, including in EBOV ( Strong et al, 2008 ; Johnson et al, 2014 ), but the detailed mechanisms of interactions between MAP kinases and EBOV remain ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the angiomotin-like 1 protein interacts with the parainfluenza virus 5 (PIV5) M protein [ 34 ] and acts as a linker between the PIV5 M and NEDD4 ubiquitin ligases [ 35 ], which reveals a novel host factor recruitment strategy for paramyxoviruses to achieve VLP production and virus budding. Moreover, a recent study showed that annexin A2 interacting with the measles virus (MeV) M protein mediates the plasma membrane localization of the M protein and assists the assembly and budding of progeny virions [ 36 ]. All of these findings accelerate our understanding of the potential functions of paramyxovirus M proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2, which belongs to the annexin superfamily, is predominantly expressed at the plasma membrane but is also present on intracellular vesicles and in the nucleus (27). Annexin A2 is involved in multiple cellular processes, including DNA replication, cell proliferation, cell adhesion, and apoptosis (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%